(untitled) (Global Journal of Human-Social Science, 2020)
The economic relations between China and the European countries are tightened by an intensive interdependence in different sectors mainly trades and services but decades of successful relations could be affected by the pressure risen around the development of the 5G network Recently the development of the technology of the future 5G network is having a certain effect on the relations among those countries that joined the race for the leading global position The major players in this geopolitical technological and economic affair are China and the USA therefore Europe plays an important role as well These occurrences may increase not only the strategic suppleness of powers like China India the United States and the European Union but also the weight of nourishing alignments and fruitful partnerships This research takes into consideration two fundamental elements to analyze this state of affairs the economic interdependence between China and the European countries and the protection of cybersecurity The comparative research method and the discourse analysis are employed in this research conducted examining the recent events from 2018 to January 2020 and the different approaches of the governments to the new technology